(untitled) (Eurasian Journal of Engineering and Technology, 2022)
Augmented reality (AR) and object recognition are two relatively new technologies that can be employed to improve the possibility of better human perception and understanding of the surroundings in the real world. The potential benefits of the integration of these two technologies can be found in many areas. This study synthesizes selected papers from 2017 to 2021 to provide a thorough overview of existing AR-based object recognition systems. Several selections and scanning processes were employed using the inclusion criteria on all 2020 papers acquired. However, only 48 papers met the criteria. The study discusses and highlights the challenges, motivations, and recommendations of using the combinations of these technologies. In addition, it provides a classification of the tools and hardware mentioned in the selected studies. Finally, a summarization of the general characteristics of systems and applications developed and implemented in the selected studies. This study aims to enrich the understanding of this type of AR and, hopefully, inspire researchers to assist in the development and growth of AR